Lignans: Quantitative Analysis of the Research Literature - Yeung, Andy Wai Kan; Tzvetkov, Nikolay T.; Balacheva, Aneliya A.; Georgieva, Maya G.; Gan, Ren-You; Jozwik, Artur; Pyzel, Bożena; Horbańczuk, Jarosław O.; Novellino, Ettore; Durazzo, Alessandra; Lucarini, Massimo; Camilli, Emanuela; et al. (Frontiers in Pharmacology, 2020)
The current study provides a comprehensive overview and analysis of the lignan literature. Data for the current study were extracted from the electronic Web of Science Core Collection database via the search string TOPIC=(“lignan*”) and processed by the VOSviewer software. The search yielded 10,742 publications. The ratio of original articles to reviews was 14.6:1. Over 80% of the analyzed papers have been published since the year 2000, and nearly 50% since the year 2010. Many of the publications were focused on pharmacology, chemistry, and plant sciences. The United States and Asian countries, such as China, Japan, South Korea, and India, were the most productive producers of lignan publications. Among the 5 most productive institutions was the University of Helsinki in Finland, the country that ranked 9th. Nineteen journals collectively published 3,607 lignan publications and were considered as core journals. Their impact factor did not correlate with the proportion of uncited papers. Highly cited publications usually mentioned phytoestrogen, isoflavone, daidzein, enterodiol, enterolactone, equol, genistein, isoflavonoid. Cancer (e.g., breast cancer), cardiovascular disease and antioxidation were the major themes. Clinical trials were estimated to contribute to 0.2–1.1% of the analyzed body of literature, so more of them should be conducted in future to substantiate the beneficial effects and optimal dose of lignan intake in humans. Moreover, researchers can refer to these findings for future research directions and collaborations.